High alpine sorcerers: revision of the cave wētā genus Pharmacus Pictet & de Saussure (Orthoptera: Rhaphidophoridae: Macropathinae), with the description of six new species and three new subspecies - Hegg, Danilo; Morgan-Richards, Mary; Trewick, Steven A. (European Journal of Taxonomy, 2022)
The New Zealand alpine cave wētā genus Pharmacus was first described by Pictet & de Saussure (1893) as a monotypic taxon. Three species were added to the genus by Richards in 1972. Here we clarify the status and appearance of all known species of Pharmacus. Based on morphology and mtDNA sequences we determine that the species Pharmacus brewsterensis Richards, 1972 is better placed within the genus Notoplectron Richards, 1964. We also resolve the species Isoplectron cochleatum Karny, 1935 and show that it belongs to the genus Pharmacus. Additionally, we describe six new species and three new subspecies from the southern regions of South Island, New Zealand. We provide key traits and known distributions for all known species and subspecies in this alpine genus. New combinations: Pharmacus brewsterensis Richards, 1972 becomes Notoplectron brewsterense (Richards, 1972) comb. nov.; Isoplectron cochleatum Karny, 1935 becomes Pharmacus cochleatus (Karny, 1935) comb. nov. New species and subspecies: Pharmacus cochleatus rawhiti subsp. nov., Pharmacus cochleatus fiordensis subsp. nov., Pharmacus cochleatus nauclerus subsp. nov., Pharmacus concinnus sp. nov., Pharmacus cristatus sp. nov., Pharmacus notabilis sp. nov., Pharmacus perfidus sp. nov., Pharmacus senex sp. nov. and Pharmacus vallestris sp. nov. New synonyms: Pharmacus dumbletoni Richards, 1972 = Pharmacus montanus Pictet & de Saussure, 1893 syn. nov.; Pharmacus chapmanae Richards, 1972 = Pharmacus cochleatus (Karny, 1935) syn. nov.